2020
DOI: 10.36428/revistadacgu.v12i22.330
|View full text |Cite
|
Sign up to set email alerts
|

Transparência governamental em capitais dos estados no Brasil nas contratações emergenciais para o combate da COVID-19

Abstract: O artigo objetivou avaliar a construção da transparência das informações sobre contratações emergenciais para o combate da Covid-19 pelos municípios-capitais do Brasil e sua relação com o avanço da pandemia em seus contextos locais, tomando por base os três rankings elaborados e divulgados pela Transparência Internacional Brasil (TIB) e os dados das secretarias municipais de saúde. Fez-se um estudo de casos múltiplos, de cunho exploratório-descritivo e de caráter qualitativo-quantitativo. Os dados mostram que … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
1
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 2 publications
1
2
1
8
Order By: Relevance
“…For such, Figure 3 100) from the second to the sixth surveys; Alagoas stood out negatively since it figured at the low level in one of the surveys and at the opaque level in the other five. This scenario, in which only two states obtained the maximum score for the ITVC-19, agrees with the findings by Pinho et al (2020) because it made evident that transparency is a challenge for the country, given that the desirable data about the transparency process of the vaccination in the country were not available and/or open to the public. This is a context in which the absence of commitment to transparency prevents the provision of information capable of making the states susceptible to criticism regarding the transparency of the vaccination process against COVID-19 (Michener et al, 2018).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…For such, Figure 3 100) from the second to the sixth surveys; Alagoas stood out negatively since it figured at the low level in one of the surveys and at the opaque level in the other five. This scenario, in which only two states obtained the maximum score for the ITVC-19, agrees with the findings by Pinho et al (2020) because it made evident that transparency is a challenge for the country, given that the desirable data about the transparency process of the vaccination in the country were not available and/or open to the public. This is a context in which the absence of commitment to transparency prevents the provision of information capable of making the states susceptible to criticism regarding the transparency of the vaccination process against COVID-19 (Michener et al, 2018).…”
Section: Discussionsupporting
confidence: 87%
“…Such research includes the study by Machado et al (2020), who, upon investigating if the measures that eased deadlines and procedures for fulfilling requests for information in the pandemic period had a significant impact on 5 of 17 subnational governments, concluded that the right to access to public information is fragile and permanently tensioned in the country. In another study, Pinho et al (2020) found non-compliance with the statutory requirements of transparency of the data on the provision of essential and desirable information on the emergency contracts for tackling COVID-19 in some capital municipalities surveyed. Raupp and Pinho (2020, p. 3725) analyzed the construction of transparency about COVID-19 by the Brazilian states and, "even if the data may reveal a concern of some governments with building better conditions for making information on the new coronavirus available", understood that "the states must still evolve in information transparency".…”
Section: Transparency In a Time Of Crisismentioning
confidence: 96%
“…Fonte: Dados da pesquisa (2021) A necessidade que os entes governamentais tem de evoluir em relação à transparencia sobre a pandemia da Covid-19, de questões sanitárias às contratações emergenciais, é um ponto comum nesses estudos. Por outro lado, tem-se a noção de que se trata de um cenário cuja magnitude e implicações afetaram praticamente toda a população, e mesmo que os governos tenham se mobilizado a darem respostas em tempo ceĺere à sociedade , não havia um gabinete digital especıŃico estruturado para tais emergencias, mesmo já existindo uma infraestrutura de transparencia (Pinho et al, 2020).…”
Section: Quadro 1 -Estudos Correlatosunclassified
“…Dentre essas, pode-se citar Machado et al (2020), que ao investigarem se as medidas que flexibilizaram prazos e procedimentos para o atendimento de pedidos de informação no período pandêmico tiveram impacto nos governos subnacionais, concluíram que o direito de acesso à informação pública é frágil e permanentemente tensionado no país. Em outro estudo, Pinho et al (2020) constataram o não cumprimento dos requisitos legais de transparência dos dados sobre a disponibilização de informações essenciais e desejáveis nas contratações emergenciais para enfrentamento da Covid-19 em alguns municípioscapitais pesquisados.…”
Section: Transparência Em éPoca De Criseunclassified